Environmental management accounting: a study of manufacturing companies in Malaysia - Dayana binti Jalaludin (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2010)
Interest in managing environmental issues has important implications on the practice of management accounting among business organizations. Environmental management accounting (EMA) promises better internal management and decision making as it explicitly addresses environmental information, particularly pertaining to costs and revenue. EMA has a financial component known as monetary environmental management accounting (MEMA) as well as a physical component known as physical environmental management accounting (PEMA). The objectives of this study are twofold; first, to examine factors that influence EMA adoption, and second, to investigate the relationship between environmental performance, economic performance and EMA adoption. By utilizing institutional theory and contingency theory, this study investigates the influence of institutional pressure (i.e. coercive isomorphism, mimetic processes and normative pressure), size, environmental sensitivity and TMC on EMA adoption level. Based on the argument that environmental-related protection activities may be a source of competitive advantage and economic opportunity, it is also proposed that environmental performance affects economic performance via the mediating variable EMA. Accordingly, better environmental performance leads to a high EMA adoption level, which, in turn, increases economic performance. The respondents of this study consisted of 74 accountants and 88 environmental managers from manufacturing companies in Malaysia. To test the proposed relationships, the study adopts an explanatory mixed methods research approach. In this study, data is first collected using a mail questionnaire followed by semi-structured interviews with a few respondents who participated in the survey. The results of the multiple regression analyses indicate that normative pressure and TMC influence EMA adoption level. However, the multiple regression analyses did not provide enough evidence to support the influence of mimetic processes, coercive isomorphism, size and environmental sensitivity on EMA adoption level. The results of the mediated regression analyses offer partial support for the hypothesized relationship between EMA, environmental performance and economic performance. Next, the post survey interviews provide some support for the survey results on normative pressure, TMC and mimetic processes. The findings from the interviews also suggest some explanation on the unexpected survey results on coercive isomorphism, size and environmental sensitivity. Additionally, the interviews uncovered several reasons for the limited role of EMA as a mediating variable in the proposed relationships. Overall, the findings of this study are particularly relevant in light of the many roles that can be played by the policy makers, especially the government, accounting educators and professional bodies in promoting EMA. More importantly, the findings of this study have implications for the benefits of EMA in supporting eco-efficiency for companies moving towards a sustainable business environment.